Investigation of physical and chemical properties of Batman’s stone - Tutumlu, Hakan; Aydoğmuş, Ercan (Yildiz Technical University, 2022)
The widespread use of special stones in the construction industry in recent years makes it necessary to know the properties of these stones well. The stones extracted in Batman region can be used in many areas in the construction sector. It is very important to characterize the physical and chemical properties of these stones and use them under optimum conditions for their successful commercialization. Stone samples were taken from the mine in Batman region; many properties such as porosity, capillary coefficient, thermal conduction coefficient, sound velocity propagation, Shore D hardness test, compressive strength, bending strength, bulk, and grain density were determined. The chemical composition and ratios of Batman stone were determined by XRF analysis. It is seen that this stone is preferred especially in buildings due to its mechanical, thermal, and economic properties. According to the measurement results obtained, as the bulk density of the stone increased, its porosity and thermal conductivity coefficient decreased. It has been observed that as the density increases, the porosity decreases, and Shore D hardness values also tend to increase. The results obtained in the experimental studies and the values found in the theoretical models were compared with statistical analysis. Copyright 2022, Yıldız Technical University.
Keywords: Analysis; Batman’s Stone; Chemical Properties; Mathematical Modeling; Thermal Conductivity Statistical